Application of Intervention Mapping to develop a community-based health promotion pre-pregnancy intervention for adolescent girls in rural South Africa: Project Ntshembo (Hope) - Draper, Catherine E (BioMed Central, 2014)
BACKGROUND: South Africa (SA) is undergoing multiple transitions with an increasing burden of non-communicable diseases and high levels of overweight and obesity in adolescent girls and women. Adolescence is key to addressing trans-generational risk and a window of opportunity to intervene and positively impact on individuals’ health trajectories into adulthood. Using Intervention Mapping (IM), this paper describes the development of the Ntshembo intervention, which is intended to improve the health and well-being of adolescent girls in order to limit the inter-generational transfer of risk of metabolic disease, in particular diabetes risk. METHODS: This paper describes the application of the first four steps of IM. Evidence is provided to support the selection of four key behavioural objectives: viz. to eat a healthy, balanced diet, increase physical activity, reduce sedentary behaviour, and promote reproductive health. Appropriate behaviour change techniques are suggested and a theoretical framework outlining components of relevant behaviour change theories is presented. It is proposed that the Ntshembo intervention will be community-based, including specialist adolescent community health workers who will deliver a complex intervention comprising of individual, peer, family and community mobilisation components. CONCLUSIONS: The Ntshembo intervention is novel, both in SA and globally, as it is: (1) based on strong evidence, extensive formative work and best practice from evaluated interventions; (2) combines theory with evidence to inform intervention components; (3) includes multiple domains of influence (community through to the individual); (4) focuses on an at-risk target group; and (5) embeds within existing and planned health service priorities in SA.